Synergism of Bacillus subtilis and Azospirillum brasilense for enhanced N-use efficiency and maize growth: Evidence from 15N isotopic and physiological responses - Galindo, Fernando Shintate [UNESP]; Thiengo, Cassio Carlette; Pagliari, Paulo Humberto; Bernardes, João Victor Silva; dos Santos, Gustavo Duprat; Longato, Pedro Augusto Fedato; Vilela, Lucila de Sousa [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Lavres, José (Wiley, 2025)
We explored the impact of inoculating maize (Zea mays L.) seeds with plant growth-promoting rhizobacteria (PGPR - Bacillus subtilis and Azospirillum brasilense), either individually or in combination, under different nitrogen input levels – control, low, average and high N levels (0, 30, 60, 90 and 120 mg L-1 equivalent to between 0 and 240 kg N ha-1) in a greenhouse setting. Leaf- and plant-level biometrics, nutritional, biochemical, and physiological evaluations were supplemented by isotopic methods (15N isotope dilution and natural abundance - δ15N‰) along with root scanning to investigate N acquisition and distribution. Dual inoculation not only enhanced the recovery of applied N but also bolstered nitrogenase activity, leading to increased biological N fixation (BNF) even at an average level of N (120 kg N ha-1). In instances where dual inoculated plants were grown at low (60 kg N ha-1) and average N levels, a cascade effect was observed, such as encompassing root growth stimulation, enhanced fertilizer and soil exploitation, and increased biomass production. Increasing N application to 240 kg N ha-1 reduced plant biomass by 19–47% compared to 120 kg N ha-1, depending on inoculation strategy. This led to downregulation of nitrogenase activity, diminished PGPR efficiency, and a significant decline in BNF. This study shows how a change in the rhizosphere microbial population can influence a myriad of responses inside the plants. Our research provides valuable insights for studies using 15N isotopic and dual inoculation techniques, offering strong potential for practical implementation.